Effects of Nitrogen Application on Root Length and Grain Yield of Rain‐Fed Maize under Different Soil Types. (1st July 2016) - Feng, Guozhong; Zhang, Yongjie; Chen, Yanling; Li, Qian; Chen, Fanjun; Gao, Qiang; Mi, Guohua
Abstract : The effect of fertilizer N on maize ( Zea mays L.) root size has been reported with inconsistency. It remains unclear whether a quantitative relationship exists between soil NO3 –N and root growth under field conditions. A 3‐yr field experiment was conducted in three soils (loamy clay, clay loam, and sandy loam) with five N treatments (from 0–312 kg N ha −1 ). Soil NO3 –N concentration and total root length were determined to a depth of 60 cm at the silking stage. It was found that plants grown in clay loam soil had larger root size compared with the other two soil. A weak parabolic relationship between N supply and root length was found in loamy clay and clay loam soil, but not in sandy loam soil. There was a parabolic relationship between soil NO3 –N concentration in the 0‐ to 60‐cm depth and total root length per plant. This relationship was mostly found in clay loam soil. Across soils and years, there was a parabolic relationship between root length density (RLD) and shoot dry matter (DM) at silking and between RLD at silking and grain yield with fertilizer N rate £240 kg N ha −1 . It is suggested that it may be not practical to regulate total root length by simply adjusting N fertilizer amount. Total root length is not relevant to maize yield under excess N input conditions. Core Ideas Plants grown in clay loam soil had larger root than in loamy clay and sandy loam soils. A parabolic relationship between soil nitrate‐N concentration and total root length. A weak parabola relationship between N supply and root length was found in loamy clay soil and clay loam soil, but not in sandy loam soil. Root length and the maximum yield reached synchronously at optimum N rates (168–240 kg N ha −1 in the present study).